Synergistic effects of oat β-glucan combined with ultrasound treatment on gel properties of silver carp surimi - Xueli He; Honglei Zhao; Yongxia Xu; Shumin Yi; Jianrong Li; Xuepeng Li (Ultrasonics Sonochemistry, 2023)
The effect of oat β-glucan (OG) combined with ultrasound treatment on the gelation properties of silver carp surimi with different salt contents was investigated. The results demonstrated that the gelation properties of surimi gels at high salt concentration were superior than those at low salt level. The addition of OG or ultrasound treatment could significantly enhance the texture properties, gel strength and water holding capacity (WHC) of gel samples, regardless of salt contents. The ultrasound treatment improved the whiteness of surimi gels, whereas the OG addition slightly declined the whiteness. Both OG addition and ultrasound treatment markedly reduced the total sulfhydryl content (total SH) and strengthened the hydrophobic interactions, forming the more uniform and denser gel network structures, hence more water was captured in network structures and became immobilized. Moreover, the combined treatment of OG and ultrasound showed synergic action on the gelation properties of surimi, and the gel strength and WHC of low-salt surimi gel treated by the combination of OG and ultrasound were even superior than that of high-salt gel without OG by traditional heating.